Analisis Peralatan Beton Ready Mix Pada Pekerjaan Pengecoran Balok Dan Lantai Proyek Gedung Education Center FISIP UNHAS - Jeri Anditia. S; Junus Mara; Lintje Tammu Tangdialla (Program Studi Teknik Sipil UKI Paulus-Makassar, 2022)
In the casting work of beams and plates on the 8th floor of the unhas FISIP Education Center building construction project using ready mix concrete produced in batching plants with dry mixed type which is then distributed to the project site using Hino Ranger FM 260 JM truck mixer capacity of 7 m3. The casting process uses a concrete pump tool with the IHI IPF100B-6N29 model with a capacity of 10-100 m3. This research was conducted to find out the effectiveness of the equipment used. From the results of the analysis conducted it can be known that the composition of the equipment used experienced a loss of production, especially in the truck mixer so that idle time occurred on the tool, therefore correction was made and from the results of calculations carried out it was proposed to reduce 3 units of truck mixers that previously there were 11 units used. Truck mixer reduction is done to reduce idle time on the equipment so that the tool can work more efficiently. From the results of research that has been done, it can be concluded that the composition of the equipment used has lost production, especially in truck mixers. Once corrected, it is proposed that the composition of the equipment is effective by reducing the use of truck mixers so as to reduce the waiting time (idle time) for pumping so that the performance of the tool can work more optimally.